Native chemical ligation approach to sensitively probe tissue acyl-CoA pools. Issue 7 (21st July 2022) - James, Andrew M.; Norman, Abigail A.I.; Houghton, Jack W.; Prag, Hiran A.; Logan, Angela; Antrobus, Robin; Hartley, Richard C.; Murphy, Michael P.
Summary: During metabolism, carboxylic acids are often activated by conjugation to the thiol of coenzyme A (CoA). The resulting acyl-CoAs comprise a group of ∼100 thioester-containing metabolites that could modify protein behavior through non-enzymatic N -acylation of lysine residues. However, the importance of many potential acyl modifications remains unclear because antibody-based methods to detect them are unavailable and the  in vivo concentrations of their respective acyl-CoAs are poorly characterized. Here, we develop cysteine-triphenylphosphonium (CysTPP), a mass spectrometry probe that uses "native chemical ligation" to sensitively detect the major acyl-CoAs present in vivo through irreversible modification of its amine via a thioester intermediate. Using CysTPP, we show that longer-chain (C13–C22) acyl-CoAs often constitute ∼60% of the acyl-CoA pool in rat tissues. These hydrophobic longer-chain fatty acyl-CoAs have the potential to non-enzymatically modify protein residues. Graphical abstract: Highlights: LC-MS/MS probe to detect the acyl moiety of thioesters using native chemical ligation Development of a quantitative and sensitive assay for ∼60 acyl-Co-As in vivo Longer-chain (C13–C22) acyl-Co-As often represent ∼60% of tissue acyl-CoA pools These longer-chain acyl-Co-As can modify protein in vitro Abstract : Acyl-Co-As can modify protein through non-enzymatic acylation. By using a novel mass spectrometry probe, James et al. demonstrate that longer-chain (C13–C22) acyl-Co-As often constitute ∼60% of the acyl-CoA pool in tissues.